The impact of a national COVID-19 lockdown on acute coronary syndrome hospitalisations in New Zealand (ANZACS-QI 55) - Daniel ZL. Chan; Ralph AH. Stewart; Andrew J. Kerr; Bridget Dicker; Campbell V. Kyle; Philip D. Adamson; Gerry Devlin; John Edmond; Seif El-Jack; John M. Elliott; Nick Fisher; Charmaine Flynn; et al. (Elsevier, 2020)
Background: Countries with a high incidence of coronavirus 2019 (COVID-19) reported reduced hospitalisations for acute coronary syndromes (ACS) during the pandemic. This study describes the impact of a nationwide lockdown on ACS hospitalisations in New Zealand (NZ), a country with a low incidence of COVID-19. Methods: All patients admitted to a NZ Hospital with ACS who underwent coronary angiography in the All NZ ACS Quality Improvement registry during the lockdown (23 March - 26 April 2020) were compared with equivalent weeks in 2015-2019. Ambulance attendances and regional community troponin-I testing were compared for lockdown and non-lockdown (1 July 2019 to 16 February 2020) periods. Findings: Hospitalisation for ACS was lower during the 5-week lockdown (105 vs. 146 per-week, rate ratio 0•72 [95% CI 0•61-0•83], p = 0.003). This was explained by fewer admissions for non-ST-segment elevation ACS (NSTE-ACS; p = 0•002) but not ST-segment elevation myocardial infarction (STEMI; p = 0•31). Patient characteristics and in-hospital mortality were similar. For STEMI, door-to-balloon times were similar (70 vs. 72 min, p = 0•52). For NSTE-ACS, there was an increase in percutaneous revascularisation (59% vs. 49%, p<0•001) and reduction in surgical revascularisation (9% vs. 15%, p = 0•005). There were fewer ambulance attendances for cardiac arrests (98 vs. 110 per-week, p = 0•04) but no difference for suspected ACS (408 vs. 420 per-week, p = 0•44). Community troponin testing was lower throughout the lockdown (182 vs. 394 per-week, p<0•001). Interpretation: Despite the low incidence of COVID-19, there was a nationwide decrease in ACS hospitalisations during the lockdown. These findings have important implications for future pandemic planning. Funding: The ANZACS-QI registry receives funding from the New Zealand Ministry of Health.